Soil CO2 flux maps as tools to reduce the risk on soil diffuse degassing areas - Viveiros, Fátima; Silva, Catarina; Goulart, Catarina; Gaspar, João L.; Ferreira, Teresa (Frontiers in Earth Science, 2024)
Carbon dioxide released permanently from soils in diffuse degassing areas may constitute a permanent hazard for the population. Several villages in the Azores archipelago (Portugal) are placed in areas with anomalous soil CO2 degassing and lethal indoor CO2 concentration (>10 vol%) has been already recorded in some buildings. The 2021-2022 dislodgements of population at Vulcano (Italy) and La Palma (Spain) volcanic islands due to high soil CO2 degassing highlight the importance of defining criteria to produce human CO2 exposure risk maps, which are useful to mitigate the risk and should constitute valuable tools for land-use planners. Risk is assessed in the current study by combining susceptibility, exposure, and vulnerability maps. The defined criteria were applied to two villages in Furnas Volcano (São Miguel Island, Azores), showing that 58% and 98% of the buildings, respectively, at Furnas and Ribeira Quente villages are at high risk of CO2 exposure.